The prevalence of diabetes and associated risk factors among adult population in a Turkish population (Trabzon city). Issue 4 (August 2022) - Nuhoglu, İrfan; Deger, Orhan; Topbaş, Murat; Erem, Cihangir
Abstract: Objective: The objectives of this study were to determine the prevalence of diagnosed and undiagnosed diabetes mellitus (DM) and prediabetes, and to evaluate the associated risk factors in a sample of adult Turkish population. Methods: A total of 4000 eligible study subjects, aged 20 years or older, chosen by multistage sampling on a field were considered. Of those 3721 subjects (2139 women and 1582 men) participated in the study. Results: The prevalence of prediabetes and DM were found to be as 6.4% and 10.4% (3.6% being newly diagnosed by this study), respectively. In multivariate logistic regression analysis, advanced age (OR:26.7, p < 0.0005 in the group 70 years and over), marriage (OR:2.05, p = 0.047), housewives (OR:1.34, p = 0.003), family history of diabetes (OR:2.84, p < 0.0005), overweight (OR:1.61, p = 0.026), obesity (OR:2.25, p < 0.0005), hypertension (OR:1.42, p = 0.007) and dyslipidemia (OR:1.38, p = 0.028) were independent risk factors for being diabetic. Conclusions: DM is an important health problem in the adult population of Trabzon city. Newly diagnosed diabetic patients who were unaware of their status are at high risk. To control DM and associated risk factors, effective public health education and taking urgent steps are needed. Highlights: Diabetes mellitus is a major global public health problem nowadays. Turkey has the highest prevalence of diabetes (12.8 %) in Europe. The prevalence of diabetes in Trabzon province have significantly increased by 73% in the last two decades. Approximately one-thirds of diabetic patients are aware of their status. Physical inactivity, being overweight, being a housewife, and central obesity are reversible risk factors for development of new diabetes.